Mothers in public and political life (Demeter Press, 2017)
Even though in most nations women are at least almost half of the population, in very few countries do they occupy a similar space in the formal institutions of political power. They are said to lack a key element for a successful career in public life: time. From this perspective, no one is worse off than women who are mothers. From another perspective, however, motherhood is thought to help politicize women, as this life-changing experience makes them aware of the limitations of some specific public policies (such as child-care, parental leave, gendered labor practices etc.) as well as more.